Pengaruh Fleksibilitas Jam Kerja dan Work Life Balance terhadap Peningkatan Produktivitas Karyawan Gen Z - Reisya Aulia Anhar; Adhila Suryaningsih; Raysha Naya Putri Fadillah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Generation Z, with unique characteristics such as technological savvy, preference for work flexibility, and need for work life balance, brings a new paradigm in human resource management. Their dominance in the workforce creates challenges as well as opportunities for companies to create a work environment that supports employee productivity and well-being. This study aims to analyze the effect of flexible working hours and work life balance on the productivity of Gen Z employees through a literature study approach. The results show that flexible working hours allow employees to work more efficiently according to their convenient time and place, while work life balance helps reduce stress, increase motivation, and drive productivity. Generation Z highly values ​​this balance, which not only improves their mental and physical well-being but also contributes to the success of the company.